Majas Dan Makna pada Lirik lagu “Seperti Tulang” Karya Nadin Amizah - Shadrina Kaysa Mazaya; Dea Putri Ananda (Jurnal Pendidikan, Bahasa dan Budaya, 2022)
The purpose of making this journal is to analyze the figure of speech and the meaning contained in the lyrics of Nadin Amizah's song entitled "Like Bones". Researchers are interested in analyzing the lyrics of the song "Like Bones" because it contains words that are both unique and beautiful and have meanings that can be interpreted. In addition, researchers are interested in identifying what figure of speech is contained in the lyrics of the song, because the lyrics of this song have meanings and expectations that want to be informed directly and indirectly. After that, the procedure used in this research is a qualitative descriptive procedure, which is a procedure with the method of analyzing information and the results of the information after it is processed into the form of descriptive text. The subjects analyzed were in the form of song lyrics titled "Like Bones". The results of the analysis of the lyrics of this song show that there are personifications, rhetorical figures of speech, and paradoxical figures of speech. The meaning and meaning contained in lyrics of the song "Like Bones" is the story of someone good at hiding wounds even though he is often seen laughing.